Longitudinal changes in sarcopenia was associated with survival among cirrhotic patients - Jiang, Minjie; Hua, Xin; Wu, Muchen; Wu, Jing; Xu, Xiaotong; Li, Juan; Meng, Qinghua (Frontiers in Nutrition, 2024)
Sarcopenia is common in patients with liver cirrhosis and is an independent predictor of multiple clinical outcomes. Most studies to date have used a static assessment of sarcopenia. However, there is very limited data evaluating the temporal course of muscle area in cirrhosis. To bridge this gap in clinical studies, we performed a longitudinal analysis to evaluate the impact of changes in sarcopenia for cirrhotic patients.Adult patients with clinically diagnosed liver cirrhosis who underwent at least 2 abdominal computed tomography (CT) scans in the hospital were enrolled. The interval between the two abdominal scans was 6±1 months. Patients were categorized into persistent non-sarcopenia, new-onset sarcopenia, sarcopenia to non-sarcopenia, and persistent sarcopenia based on changes in sarcopenia. Kaplan-Meier method and Logrank tests were used to separately compare unadjusted survival curves by different statuses of sarcopenia. Cox regression analysis was performed to assess the associations between different states of sarcopenia and overall mortality. The association between persistent non-sarcopenia and new-onset sarcopenia was analyzed by multivariate logistic regression analysis.A total of 307 patients were included for analysis. At the second assessment, 10.10% (31/307) patients were new-onset sarcopenia, 27.69% (85/307) with persistent sarcopenia status, while 13.03% (40/307) patients with sarcopenia developed nonsarcopenia and 49.19% (151/307) with persistent non-sarcopenia status. The overall survival rate was significantly lower in the persistent sarcopenia and new-onset sarcopenia than in the non-sarcopenia group and sarcopenia to non-sarcopenia group (P<0.001). Persistent sarcopenia (HR 5.799, P=0.009) and new onset sarcopenia (HR 5.205, P=0.010) were identified as poor prognostic factors for cirrhotic patients. The etiology of cirrhosis and the initial skeletal muscle mass were independent risk factors for new-onset sarcopenia.Sarcopenia is a dynamically changing process in patients with cirrhosis. Persistent and new-onset sarcopenia were independently and robustly associated with overall survival.